Analisis Pembalikan Beban Pembuktian dalam Penyelesaian Sengketa Konsumen ditinjau dari Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen dan Hukum Acara Perdata - Dyah Putri Purnamasari; Khoidin _ (JURNAL RECHTENS, 2013)
The most important part of the procedural law is a matter of proof for a claim is acceptable or not depens on the evidence submitted by the parties in the proceedings in the court. In order to provide protection to consumers harmed by consumsing the goods or service producedby businesses, act No. 8 of 1999 on consumer protection set about proving system that is specifically used in any consumer dispute resolution through the judicial reversal of the burden of proof.